ta thay x bới [tex]\frac{1}{x}[/tex]
ta được [tex]4f(\frac{1}{x})+5f(x)+\frac{9}{x}=0[/tex]
kết hợp với giả thiết ta được hệ phương trình
[tex]\left\{\begin{matrix} 4f(x)+5f(\frac{1}{x}) +9x=0& \\ 5f(x)+4f(\frac{1}{x})+\frac{9}{x}=0 & \end{matrix}\right. \Rightarrow 9f(x)+\frac{45}{x}-36x=0<=>f(x)=4x-\frac{5}{x}[/tex]
thay vào lim
[tex]\lim_{x \rightarrow 2}\frac{\sqrt{4x^2+9}-5}{(x-2)(x+1)}=\lim_{x \rightarrow 2}\frac{\frac{4(x^2-4)}{\sqrt{4x^2+9}+5}}{(x-2)(x+1)}=\lim_{x \rightarrow 2}\frac{4(x+2)}{(\sqrt{4x^2+9}+5)(x+1)}=\frac{8}{15}[/tex]